11-(x+1)²≥x
11-x²-2x-1≥x
x²+3x-10≤0
x²+3x-10=0 D=49 √D=7
x₁=2 x₂=-5
(x-2)(x+5)≤0
-∞+-5___-2++∞ ⇒
ответ: x∈[-5;2]
(2x-8)²-4x*(2x-8)≥0
(2x-8)(2x-8-4x)≥0
(2x-8)(-2x-8)≥0
-(2x-8)*(2x+8)≥0 |÷(-1)
4x²-64≤0 |÷4
x²-16≤0
(x-4)(x+4)≤0
-∞+-4-4++∞ ⇒
ответ: x∈[-4;4].
x*(x+5)-2>4x
x²+5x-2-4x>0
x²+x-2>0
x²+x-2=0 D=9 √D=3
x₁=1 x₂=-2 ⇒
(x-1)(x+2)>0
-∞+-2-1++∞ ⇒
ответ: x∈(-∞-2)U(1;+∞).
(1/3)*x²+3x+6<0 |×3
x²+9x+18<0
x²+9x+18=0 D=9 √D=3
x₁=-3 x₂=-6 ⇒
(x+3)(x+6)<0
-∞+-6--3++∞ ⇒
ответ: x∈(-6;-3).
x>(x²/2)-4x+5¹/₂
x>(x²/2)-4x+11/2 |×2
2x>x²-8x+11
x²-10x+11<0
x²-10x+11=0 D=56 √D=√56
x₁=5-√14 x₂=5+√14
-∞+5-√14-5+√14++∞ ⇒
ответ: x∈(5-√14;5+√14).
Тогда х+12 км/ч скорость второго
Через 4 часа они проедут
4х км первый
4(х+12) км второй
И им останется ещё 80 км
Составим уравнение
4х+4(х+12)+80=500
4х+4х+48+80=500
8х=500-80-48
8х=372
Х=372:8
Х=46,5
46,5 км/скорость первого
1) 46,5+12=58,5 км/ч скорость второго